MIKROENKAPSULASI ASAP CAIR KAYU LABAN (Vitex pubescens) DENGAN METODE PENGERINGAN SPRAY DRYING DAN FOAM MAT DRYING - , RAHMI AZZAHRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Laban wood (Vitex pubescens) is a type of hardwood that used for charcoal and smoked food production in East Kalimantan. Liquid smoke from laban wood has bioactive compounds such as acids, phenols and carbonyls. Microencapsulation use for minimizing the damage levels of bioactive compounds in liquid smoke. Therefore, it needs encapsulated. This research was aim to know the contents of acids, phenols, carbonyls, water, particle size and volatile compounds in microcapsule of laban woodâs liquid smoke redistillate and also to know the best drying microencapsulation method. In this research, the microcapsule from laban wood liquidâs smoke redistillate production by spray drying and foam mat drying methods would be analyzed such as content of acid, phenols and carbonyls, water, particle size and the profile of volatile compounds. The results showed the highest content of total acid, phenols, carbonyls, water and volatile compounds is the microcapsule of laban woodâs liquid smoke redistillate from spray drying method. The particle size of microcapsules from the different methods, were not vary much and the best drying method for laban woodâs liquid smoke redistillate microencapsulation is spray drying.